English Pre-service Teachers Drop out: A Case Study - Narváez Trejo, Oscar Manuel; Núñez Mercado, Patricia; Cruz Martínez, Cliserio Antonio; Estrada Sánchez, Gabriela Guadalupe (Emerging Trends in Education, 2023)
Higher education institutions in Mexico face an early leaving phenomenon as one of their main challenges. This is why the main objective of this qualitative, transversal, descriptive research was to identify the reasons causing the students’ early leaving in an ELT teacher education program, so as to find strategies to deal with this problem. Institutional documents on students’ dropping out were systematically consulted and ten former students of a BA in English Language in a state university in the southeast of Mexico were interviewed in-depth. Data were analyzed using a content analysis approach. Results indicate that causes influencing undergraduate students’ decision of dropping out are multifactorial, and among them the most salient are related to a poor choice of a degree program, the faculty and school administration. Keywords: dropping out; teacher education; pre-service teachers; ELT; México.